Impact of mobile phone dependence on behavior and academic performance of adolescents in selected schools of Uttarakhand, India - Mahendra Singh Yadav; S Malar Kodi; Rupinder Deol (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Mobile phones are one of the excellent gifts of technology in the 21st century, which is most popular among adolescents. Today, mobile phones have infinite resources that have multiple benefits and applications. Its excessive use may impact adolescents in the form of behavioral changes and diminish the academic performance. This study explores the relationship between mobile phone usage with behavioral modifications and educational achievement among adolescents. MATERIALS AND METHODS: A descriptive correlational study was conducted among adolescents (n = 285 -male-210, female-75) at selected schools of Rishikesh, Uttarakhand, India. The test of mobile dependence was used to assess the mobile phone dependence, and a behavioral Likert scale to evaluate the behavioral changes through the self-report method. The academic performance was observed by school records; percentage of the last two examination results was considered. Collected data were analyzed using descriptive and inferential statistics. RESULTS: The study shows that 156 (54.70%) participants had a low mobile dependency, 191 (67%) participants had negative behavioral changes, and 125 (43.90%) participants had shown reduced academic performance due to overuse of the mobile phone. A significant relationship was seen between mobile phone dependency with behavioral changes (P < 0.001) and academic achievement (P < 0.035) seen among adolescents. Regression analysis predicted 49% of the differences among adolescents with selected variables due to the overuse of mobile phones. CONCLUSION: The study concluded that mobile dependency changes adolescent's behavior as well as reduces their academic performance due to the overuse of the mobile phone.